2008
DOI: 10.1016/j.psyneuen.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion recognition and amygdala activation are associated with menstrual cycle phase

Abstract: Converging evidence has accumulated that menstrual cycle and thus hormonal levels can affect emotional behavior, in particular facial emotion recognition. Here we explored the association of ovarian hormone levels and amygdala activation during an explicit emotion recognition task in two groups of healthy young females: one group was measured while in their follicular phase (n=11) and the other during their luteal phase (n=11). Using a 3T scanner in combination with a protocol specifically optimized to reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 48 publications
8
115
2
1
Order By: Relevance
“…Changes in emotion recognition across the menstrual cycle have not been well investigated yet, but the obtained results are in line with the ones of Derntl et al (2008). They observed better facial expressions recognition in the follicular phase than in the luteal phase, a negative correlation between levels of progesterone and recognition accuracy, and stronger activation of the amygdala in the follicular phase.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Changes in emotion recognition across the menstrual cycle have not been well investigated yet, but the obtained results are in line with the ones of Derntl et al (2008). They observed better facial expressions recognition in the follicular phase than in the luteal phase, a negative correlation between levels of progesterone and recognition accuracy, and stronger activation of the amygdala in the follicular phase.…”
Section: Discussionsupporting
confidence: 78%
“…However, more accurate recognition in the follicular phase compared to the luteal has not been consistently found for all basic emotions (Guapo et al, 2009). Furthermore, some researchers showed stronger amygdala response in the low progesterone phase (Derntl et al, 2008), while some observed stronger amygdala reactivity to angry and fearful faces after the progesterone administration (Van Wingen et al, 2007). To conclude, the available findings indicate a more accurate emotion recognition in the follicular phase in comparison to the luteal phase, but there is still inconsistency and lack of knowledge regarding this topic.…”
Section: Emotion Recognitionmentioning
confidence: 99%
“…Moreover, there is some evidence that emotional face perception in general is affected by sex hormones (Pearson and Lewis, 2005;Conway et al, 2007;Derntl et al, 2008). For example, higher accuracy for detecting fearful faces was found during late preovulatory phase, when estrogen levels are high, than during menstruation when estrogen levels are low (Pearson and Lewis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in another study, recognition accuracy for emotional expressions was increased in women in their follicular phase when progesterone levels are low relative to the luteal phase when progesterone levels are elevated (Derntl et al, 2008). In addition, amygdala activation in response to fearful faces was negatively correlated with progesterone levels, indicating greater amygdala activation is associated with lower progesterone levels (Derntl et al, 2008). Thus, the interaction of the amygdala and fluctuating progesterone levels across the human menstrual cycle in the regulation of affective cognition, remains unclear.…”
Section: Hormonal Contribution To Affective Psychopathologies Across mentioning
confidence: 73%
“…For example, memory recall of threatening images increased during a stressor task in women with high levels of progesterone when tested at the mid-luteal phase of menstrual cycle relative to women with low levels of progesterone tested Hormonal contribution to affective psychopathologies across species 24 during their non-luteal phase or compared to control participants who were not exposed to stressors (Felmingham et al, 2012). By contrast, in another study, recognition accuracy for emotional expressions was increased in women in their follicular phase when progesterone levels are low relative to the luteal phase when progesterone levels are elevated (Derntl et al, 2008). In addition, amygdala activation in response to fearful faces was negatively correlated with progesterone levels, indicating greater amygdala activation is associated with lower progesterone levels (Derntl et al, 2008).…”
Section: Hormonal Contribution To Affective Psychopathologies Across mentioning
confidence: 94%